How sales strategy translates into performance: The role of salesperson customer orientation and value-based selling - Terho H; Eggert A; Haas A; Ulaga W (Elsevier Inc., 2022)
The role of selling has become increasingly analytical and it is a central topic on senior management's agenda in business markets. Still, sales strategy remains an under-researched topic in the business-to-business marketing domain. Very little is known about how to implement it effectively or about the mechanisms of how sales strategy affects performance, despite its apparent importance for firm success. Drawing on a large-scale sample of 816 salespeople and directors from 30 sales organizations, and employing multilevel structural equation modeling, this study sheds light on the chain of effects that transforms sales strategy as an organizational variable into selling performance captured on the individual salesperson level. The findings demonstrate that a firm's sales strategy is related to market performance and affects salesperson selling performance both directly and indirectly. Further, the results show that each sales strategy dimension affects salesperson performance in a unique way. Of the three dimensions of sales strategy studied, only segmentation directly impacts salesperson selling performance. Prioritization and selling models impact salesperson performance indirectly, via their impact on customer orientation and value-based selling. These results lead to actionable implications for the effective implementation of sales strategy in business markets. (C) 2015 Elsevier Inc. All rights reserved.